2015
DOI: 10.4049/jimmunol.1401614
|View full text |Cite
|
Sign up to set email alerts
|

A Role for APPL1 in TLR3/4-Dependent TBK1 and IKKε Activation in Macrophages

Abstract: Endosomes have important roles in intracellular signal transduction as a sorting platform. Signaling cascades from TLR engagement to IRF3-dependent gene transcription rely on endosomes, yet the proteins that specifically recruit IRF3-activating molecules to them are poorly defined. We show that adaptor protein containing a pleckstrin-homology domain, a phosphotyrosine-binding domain, and a leucine zipper motif (APPL)1, an early endosomal protein, is required for both TRIF- and retinoic acid–inducible gene 1–de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 58 publications
1
17
1
Order By: Relevance
“…Thus APPL1 and APPL2 do contribute to TLR signaling and have opposing effects on the Akt and MAPK signaling program generated by this receptor. Of note also is the LPS‐induced depletion of APPL1 protein in control cells at 30 and 60 min time points, which coincides with its LPS‐induced proteasomal degradation that is noted in another study . By varying LPS‐triggered signaling, the APPLs have the potential to modulate downstream transcriptional and cytokine responses and these were next examined.…”
Section: Resultsmentioning
confidence: 75%
See 1 more Smart Citation
“…Thus APPL1 and APPL2 do contribute to TLR signaling and have opposing effects on the Akt and MAPK signaling program generated by this receptor. Of note also is the LPS‐induced depletion of APPL1 protein in control cells at 30 and 60 min time points, which coincides with its LPS‐induced proteasomal degradation that is noted in another study . By varying LPS‐triggered signaling, the APPLs have the potential to modulate downstream transcriptional and cytokine responses and these were next examined.…”
Section: Resultsmentioning
confidence: 75%
“…Our findings are in close agreement with others. APPL1 has been shown to be responsible for IRF3‐dependent gene transcription downstream of TLR3 and TLR4 and the same study showed that it does not regulate TNF secretion . Also, in HEK239 cells, APPL1 appears to regulate the basal activity of NF‐KB , although it is not known whether this applies to macrophages.…”
Section: Discussionmentioning
confidence: 99%
“…) and TBK1 can be recruited by APPL1 to regulate IFN regulatory factor 3‐dependent gene expression in macrophages in response to viral and bacterial infections (Chau et al . ). Based on these reports, we anticipated that: (a) APPL1 could be the adaptor protein for Cdon and TBK1 and that (b) Akt is the downstream effector of the Cdon and TBK1 complex.…”
Section: Discussionmentioning
confidence: 99%
“…APPL1 can regulate the activity of Akt by direct interaction with Akt and its upstream proteins (Yang et al 2003;Lin et al 2006;Mao et al 2006;Varsano et al 2006). Other studies have reported that TBK1 can activate Akt through direct phosphorylation (Ou et al 2011;Xie et al 2011) and TBK1 can be recruited by APPL1 to regulate IFN regulatory factor 3-dependent gene expression in macrophages in response to viral and bacterial infections (Chau et al 2015). Based on these reports, we anticipated that: (a) APPL1 could be the adaptor protein for Cdon and TBK1 and that (b) Akt is the downstream effector of the Cdon and TBK1 complex.…”
Section: Tbk1 Functionmentioning
confidence: 98%
“…The endolysosome is increasingly being recognized as an important platform for innate immune signaling, including that via TLR3. Specifically, not only is the acidification of endolysosomes crucial (11), but also downstream phosphorylation and activation of IRF3 require recruitment of TBK1/IKK⑀-containing complexes to the endolysosome compartments (45,46). Although the exact mechanism(s) requires further investigation, GRP78 may control the stability of phosphorylated IRF3 resulting from TLR3 engagement by chaperoning with it.…”
Section: Discussionmentioning
confidence: 99%